The Costs of Open and Closed Access : Using the Finnish Research Output as an Example - Ilva, Jyrki; Laitinen, Markku; Saarti, Jarmo (Qualitative and Quantitative Methods in Libraries, 2017)
The Open Access movement in scientific publishing has been gathering momentum in the European Union and its member states, partly due to the policies of some of its main research funders. Already we have seen encouraging research results on the effects of openness on the dissemination of scientific outputs. As business models of Open Access publishing are still under development, the aim of our paper is to compare the costs associated with different modes of disseminating scientific publications based on the current data available. We will also analyse the potential costs associated with Open Access publishing models and compare them with the current cost structure of – mostly – paywalled access. The discussion will include a description of current Finnish Open Access policies and their funding models. The financial analysis will be based on the statistical data found in the national Research Library Statistics database and the Finnish National Research Publications database, Juuli. We will assess the alternatives on how best to develop statistical tools to estimate the true costs of scientific publishing.